Effectiveness, safety, and immunogenicity of half dose ChAdOx1 nCoV-19 COVID-19 Vaccine: Viana project - Valim, Valéria; Martins-Filho, Olindo Assis; Gouvea, Maria da Penha Gomes; Camacho, Luiz Antônio Bastos; Villela, Daniel Antunes Maciel; de Lima, Sheila Maria Barbosa; Azevedo, Adriana Souza; Neto, Lauro Ferreira Pinto; Domingues, Carla Magda Allan Santos; de Medeiros Junior, Nésio Fernandes; Moulaz, Isac Ribeiro; Dias, Laiza Hombre; et al. (Frontiers in Immunology, 2022)
Fractional dose is an important strategy to increase access to vaccines. This study evaluated the effectiveness, safety, and immunogenicity of half dose of ChAdOx1 nCoV-19 vaccine. A non-inferiority non-randomized controlled trial compared a half dose of ChAdOx1 nCoV-19 with the full dose, with an interval of 8 to 10 weeks, in 18–49 years. The primary endpoints were the incidence rate of new cases/1000 person-year at 90 days after 14 days of the second dose, confirmed by RT-PCR and new cases registered at SUS National Health Surveillance Database (e-SUS VS). The anti-SARS-CoV-2 spike (S) protein receptor binding domain (RBD) by chemiluminescence and the neutralizing antibodies by plaque reduction neutralization test (PRNT) were titrated. The soluble biomarkers were quantified with a multiplex immunoassay. Follow-up was 90 days after 14 days of the second dose. A total of 29,598 individuals were vaccinated. After exclusion, 16,570 individuals who received half a dose and 6,402 who received full doses were analyzed. The incidence of new cases confirmed by RT-PCR of half dose was non-inferior to full dose (23.7 vs. 25.7 cases per 1,000 persons-year (coefficient group -0.09 CI95%(-0.49 to 0.31)), even after adjusting for age and sex. There were no deaths or hospitalization after immunization of either group. Immunogenicity was evaluated in a subsample (N=558) compared to 154 healthcare workers who received a full dose. The seroconversion rate in seronegative individuals at baseline half dose was 99.8%, similar to that of the full dose (100%). Geometric Mean Concentration (95% CI; BAU/mL) were half dose = 188 (163-217) and full dose = 529 (423-663) (p < 0.001). In seropositive subjects at baseline (pre-immune individuals), the first dose induced very high and similar IgG-S in half dose 1,359 (1,245-1,483) and full dose 1,354 (1,048–1,749). A half dose induced a high increase in plasma chemokines, pro-inflammatory/regulatory cytokines, and growth factors. The frequency of adverse events was similar. No serious adverse events or deaths were reported. A half dose of ChAdOx1 nCoV-19 is as effective, safe, and immunogenic as the full dose. The immune response in pre-immune individuals indicates that the half dose may be a booster dose schedule.